ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEUANGAN PADA SMKS PGRI 1 KOTA JAMBI - Lestari, Ayu; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Management process of the financial administration at SMKS PGRI I Jambi City is still done manually date book that is using at the payment of spp , money computer practices , money the test and op3 ( osis , pmr , the library , scout ) so that in the management of financial administration is still take a long time and slow , inefficient , as well as the results were not accurate .The solution offered information systems that the change is based a database .As for the purpose of this research is to analyze and design systems information financial administration the successful students at smks pgri one city jambi with benefit gained that is making it easier in the management of financial administration and reporting to the school principal , and able to minimize the time, so in the management of financial administration can be done at the correct time , fast and accurate. The tools modeling a system used that is using dfd ( data flow diagram ) with an output that produced in the form of the prototype of to the reports on the reception of pay , to send daily report , the report and the report on student data as of the payment of .And in building prototypes has still not been concerned about data security system so it is suggested for subsequent development is expected to be furnished with data security